The endothelial cell receptor stabilin-2 regulates VWF-FVIII complex half-life and immunogenicity - Swystun, Laura L.; Lai, Jesse D.; Notley, Colleen; Georgescu, Ilinca; Paine, A. Simonne; Mewburn, Jeff; Nesbitt, Kate; Schledzewski, Kai; Géraud, Cyrill; Kzhyshkowska, Julia; Goerdt, Sergij; Hopman, Wilma; et al. (The Journal of Clinical Investigation, 2018)
Quantitative abnormalities of the von Willebrand factor–factor VIII (VWF-FVIII) complex associate with inherited bleeding or thrombotic disorders. Receptor-mediated interactions between plasma VWF-FVIII and phagocytic or immune cells can influence their hemostatic and immunogenic activities. Genetic association studies have demonstrated that variants in the STAB2 gene, which encodes the scavenger receptor stabilin-2, associate with plasma levels of VWF-FVIII. However, the mechanistic basis and pathophysiological consequences of this association are unknown. We have demonstrated that stabilin-2–expressing cells bind and internalize human VWF and FVIII in a VWF-dependent manner, and stabilin-2–deficient mice displayed prolonged human VWF-FVIII half-life compared with controls. The stabilin-2 variant p.E2377K significantly decreased stabilin-2 expression and impaired VWF endocytosis in a heterologous expression system, and common STAB2 variants associated with plasma VWF levels in type 1 von Willebrand disease patients. STAB2-deficient mice displayed a decreased immunogenic response to human VWF-FVIII complex, while coinfusion of human VWF-FVIII with the stabilin-2 ligand hyaluronic acid attenuated the immune response to exogenous FVIII. Collectively, these data suggest that stabilin-2 functions as both a clearance and an immunoregulatory receptor for VWF-FVIII, making stabilin-2 a novel molecular target for modification of the half-life of VWF-FVIII and the immune response to VWF-FVIII concentrates.